Influence of Sugar Palm Ash Fraction and Resonator Configuration on Acoustic Absorption Performance of Expose Brick - Zulfa Kamila R; Iwan Yahya; Utari U (INDONESIAN JOURNAL OF APPLIED PHYSICS, 2016)
Sound absorption performance optimization of expose brick has been conducted in associated with the fraction of sugar palm ash in its raw material and configuration of Helmholtz resonators inside the brick structure. The testing was conducted experimentally refer to ASTM E-1050-98 standard procedure. In this case there are three variations sugar palm ash fractions of 0%, 5%, and 10%, as well as two array resonator configurations. The results showed that the brick with fraction of 10% sugar palm ash has the best sound absorption performance. As for the configuration of array identical Helmholtz resonator giving better performance improvement at low frequency span than complex resonator structure with coupled cavity where the best performance occur on(376-488) Hz frequency range with the absorption coefficient α of 0.54.